The phallic structures in Gryllotalpidae (Orthoptera: Gryllotalpoidea), and its generic implications - Cadena-Castañeda, Oscar J. (Zootaxa, 2015)
A nomenclature for phallic structures of members of the family Gryllotalpidae is proposed. Genital structures of the main genera of mole crickets are described, discussing the relationships among subfamilies and their generic delimitation. A key is provided for separation of genera based on genitalia structure. Finally, parthenogenesis in genus Gryllotalpella is recorded for the first time.